Adaptasi e-Learning dalam Pendidikan Islam:: Membangun Pendekatan Kolaboratif-Inklusif Untuk Kemajuan Lembaga Madrasah & Pesantren di Madura - Supandi Supandi; Moh. Subhan; Abdul Hobir (Kariman: Jurnal Pendidikan Keislaman, 2024)
Adapting e-learning in Islamic Education: Building a collaborative-inclusive approach for the progress of Madrasah & Islamic Boarding School institutions in Madura has its own attraction for researchers to carry out in-depth studies, this is due to the many unique problems of the Madura region which have distinctive characteristics, then e-learning learning phenomenon applied in the education and teaching process. The research methods used are 1) qualitative approach and exploratory type, 2) location in the Madura region, 3) data collection through interviews, observation, and documentation data analysis, 4) data analysis, 5) validity and reliability, and 6) research ethics. The research results show that: 1) Implementation of e-learning adaptation includes: a) Technological infrastructure and learning accessibility have been built, but still need to be improved, b) Asatidz competencies still need to be supported, c) The students' learning skills are quite good, d) Inclusivity is under educational goals and is still worthy of optimization, e) the benefits of e-learning are: flexibility, extensive learning resources, optimal involvement of students in e-learning. 2) The results of e-learning adaptation show that: a) Increased accessibility of e-learning learning continues to increase and leads to progress, b) Implementation of education by collaboration continues to be encouraged for the progress of Madrasas and Islamic Boarding Schools, c) Increased competency of asatidz, d) The quality of learning and academic results of the students are increasing and improving, e) The challenges of e-learning vary depending on the area where the Islamic educational institution is located, f) Inclusiveness and accommodation for special needs for students providing equal space and opportunities for people with disabilities. The implications of this research are: 1) Accessibility of Islamic education is increasing, 2) Information technology skills are increasing, 3) Islamic education learning processes are becoming more qualified and flexible, 4) Collaboration in the implementation of education can be well-developed, 5) Encouraging the participation of guardians and parents and several community commodities who care about the continuity of Islamic education, 6) Open opportunities for students and students to work, innovate and be creative in the world of Islamic education openly and widely.